CROATIA’S SECESSION FROM THE SFRY AND THE SERBO-CROATIAN WAR - Dzemyanovich, Yuliya (International Journal of Innovative Technologies in Social Science, 2021)
This article is devoted to Croatia’s secession from the Socialist Federal Republic of Yugoslavia (SFRY) and the consequences of such actions. It describes the period from 1990 to January 1992. In the early 1990s, Croats began to advocate for the creation of their independent national republic. These aspirations were not supported by the Croatian Serbs, who constituted a significant percentage of the population of Croatia. Croatian Serbs were not ready to lose their links with Serbia and other Serb communities of the SFRY and to become a national minority within the Croatian state. The divergence of views on the future of Croatia led to a rapid increase in tensions between the two ethnic groups, which ultimately led to an open armed confrontation between the citizens of the same subject of the SFRY. The presence on the territory of Croatia of the Yugoslav People’s Army (JNA) worsened the situation, as JNA actively participated in the conflict on the side of the Croatian Serbs. The conflict’s parties could not independently come to a peaceful settlement. The Croats and Serbs agreed only to a temporary ceasefire and the UN peacekeeping contingent into the conflict zone. The parties made such steps only under pressure from the international community, which singled out these two conditions as necessary for international recognition of Croatia and the lifting of economic sanctions over the Federal Republic of Yugoslavia (FRY), from which Croatian Serbs were dependent.